Penentuan Umur Simpan Loloh Piduh dengan Metode Accelerated Shelf Life Testing (ASLT) Menggunakan Pendekatan Model Arrhenius - Putu Wahyu Nirmala Sari; Ida Bagus Putu Gunadnya; Gede Arda (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
The purpose of this study was to determine the shelf-life of loloh piduh packed in two different packages that is packed in plastic bottle and glass bottle. Both packed loloh piduh was stored in four temperatures, namely 15oC, 35oC 45oC 55oC. The observed parameters were pH and four sensory parameters using preference test. The sensory parameters consisted of sour taste, sweet taste, sour aroma, alcohol aroma, and turbidity. This research was conducted in 12 hours or up to 50 percent of the panelists rejected the test sample and observation was taken every two hour. The results showed that the critical quality parameters of loloh piduh packed in plastic bottles and glass bottles was sour aroma which followed zero order of kinetics reaction. Predicted shelf-life of loloh piduh packed in plastic bottles which stored at room temperature (28oC) was 9.82 hour, while the shelf life of loloh piduh packed in glass bottles that stored at the same temperature was 12.81 hours.